Gait speed and prognosis in patients with idiopathic pulmonary fibrosis: a prospective cohort study. Issue 2 (7th February 2019) - Nolan, Claire M.; Maddocks, Matthew; Maher, Toby M.; Banya, Winston; Patel, Suhani; Barker, Ruth E.; Jones, Sarah E.; George, Peter M.; Cullinan, Paul; Man, William D-C.
The 4-m gait speed (4MGS), a simple physical performance measure and surrogate marker of frailty, consistently predicts adverse prognosis in older adults. We hypothesised that 4MGS could predict all-cause mortality and nonelective hospitalisation in patients with idiopathic pulmonary fibrosis (IPF). 4MGS and lung function were measured at baseline in 130 outpatients newly diagnosed with IPF. Survival status and nonelective hospital admissions were recorded over 1 year. We assessed the predictive value of 4MGS (as a continuous variable and as a binary variable: slow versus preserved 4MGS) by calculating hazard ratios using Cox proportional regression, adjusting for potential confounding variables. Receiver operating characteristic curves assessed discrimination between the multivariable regression models and established prognostic indices. Continuous 4MGS and slow 4MGS were independent predictors of all-cause mortality (4MGS: HR 0.03, 95% CI 0.01–0.31; p=0.004; slow 4MGS: 2.63, 95% CI 1.01–6.87; p=0.049) and hospitalisation (4MGS: HR 0.02, 95% CI 0.01–0.14; p<0.001; slow 4MGS: 2.76, 95% CI 1.16–6.58; p=0.02). Multivariable models incorporating 4MGS or slow 4MGS had better discrimination for predicting mortality than either the gender, age and lung physiology index or Composite Physiologic Index. In patients with IPF, 4MGS is an independent predictor of all-cause mortality and nonelective hospitalisation. 4MGS independently predicts all-cause mortality and nonelective hospitalisation in patients with newly diagnosed IPF http://ow.ly/cT9H30mCkUr